2010
DOI: 10.1002/j.1556-6678.2010.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

The Black Student Experience at Predominantly White Colleges: Implications for School and College Counselors

Abstract: Research from higher education and cultural studies that has examined the Black college student experience at predominantly White institutions (PWIs) is presented to assist counselors in understanding how Black college students' relationships with faculty, family, friends from home, and peers in Black student organizations can become assets or liabilities to their academic achievement and persistence. Implications are provided for assisting counselors in preparing Black students for, and supporting them while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 25 publications
5
103
1
Order By: Relevance
“…However, Vallerand and Bissonnette did not assess the need for relatedness, which is a salient limitation and substantial gap that exists in the literature given recent research emphasizing the important role that relationships with college peers, faculty, and family and friends from home have in facilitating college success (for a review see Guiffrida & Douthit, 2010).…”
Section: College Student Motivation and Retention Researchmentioning
confidence: 99%
“…However, Vallerand and Bissonnette did not assess the need for relatedness, which is a salient limitation and substantial gap that exists in the literature given recent research emphasizing the important role that relationships with college peers, faculty, and family and friends from home have in facilitating college success (for a review see Guiffrida & Douthit, 2010).…”
Section: College Student Motivation and Retention Researchmentioning
confidence: 99%
“…Seifert, Drummond, and Pascarella found African American students at HBCUs reported significantly greater levels of non-classroom interactions with faculty, faculty interest in teaching and student development, number of essay exams, instructor feedback, scholarly and intellectual emphasis, and quality of interactions with other students (2006), all of which can lead to higher student engagement scores. Conversely, negative gains in African American student engagement scores have been found for students who attend PWIs due to perceived sociocultural challenges (Guiffrida & Douthit, 2010). No significant differences were detected for Level of Academic Challenge.…”
Section: African American Student Engagementmentioning
confidence: 88%
“…Overall, it has been found that African American students are unable to form strong relationships with White faculty at PWIs (Guiffrida & Douthit, 2010). This finding can be attributed to African American student perceptions at PWIs that White faculty are culturally insensitive.…”
Section: African American Student Engagement At Pwismentioning
confidence: 97%
See 1 more Smart Citation
“…In the face of countless messages of deficiency and inferiority, Black students see college as a pathway to personal and professional confidence and success (Guiffrida & Douthit, 2010;Wood, 2012). In studies by Ostrove and Long (2007) and Ostrove, Stewart, and Curtin (2011), the authors determined that students' sense of belonging within the institution was integral to their ability and desire to integrate and commit to the institution as well as the purpose and process of higher education.…”
Section: Black Youth In Collegementioning
confidence: 99%